Monitoring Current Status of and Trends in Boreal Forest Land Use in Russian Karelia - Charles Burnett; Andrew Fall; Erkki Tomppo; Risto Kalliola (Ecology and Society, 2003)
Some of the last remaining near-natural boreal forest landscapes in northern Europe can be found in the Russian Karelia near its border with Finland. Currently, these forests are facing strong exploitation pressure in the form of extensive clearcuts. Demand for conservation is also high. We characterize the boreal forest landscape in the region and assess the impacts of past and potential management actions through a mapping and modeling study that synthesizes methods from landscape ecology, remote sensing, and simulation modeling. The forests of the study area were mapped using techniques for interpreting multitemporal satellite images and detecting changes. The species composition and structure of the forests were estimated using the multisource k-nearest neighbors (k-nn) method. Forest harvesting rates and current landscape patterns were used to parameterize models built with a cell-based Spatially Explicit Landscape Event Simulator (SELES) modeling tool, and alternative land-use policy strategies were simulated with and without natural fire. Based on 10 Monte Carlo runs for each scenario, we can predict dramatic changes in the forest landscape structure after 30-70 yr. The current, complexly structured, near-natural forest assemblage will rapidly be converted into its transpose: an expanse of young regeneration stands, with blocks of near-natural forest extant only as islands within mires and in the reserve areas. The prompt establishment of the proposed Kalevala National Park is regionally important for these reasons: (1) to increase the types of near-natural forest conserved, (2) to provide a second large biodiversity source adjacent to the heavily fragmented Finnish forests, and (3) to reduce the currently inflated rate of harvesting.